Panegyric - Debord, Guy (Verso, 2004)
Guy Debord's silver-tongue-in-cheek autobiography mixes precision and pastiche in a whirlwind account of philosophy, exploit, and inebriation. From the stark professions of Volume I to the illustrated sequences of Volume 2, Panegyric confronts us with a figure who strategically, demonically tried to wrest life from the disabling modern 'spectacle.'